From Tumor Cells to Endothelium and Gut Microbiome: A Complex Interaction Favoring the Metastasis Cascade - Abdel Sater, Ali H.; Bouferraa, Youssef; Amhaz, Ghid; Haibe, Yolla; Lakkiss, Ahmed El; Shamseddine, Ali (Frontiers in Oncology, 2022)
Metastasis is a complicated process through which tumor cells disseminate to distant organs and adapt to novel tumor microenvironments. This multi-step cascade relies on the accumulation of genetic and epigenetic alterations within the tumor cells as well as the surrounding non-tumor stromal cells. Endothelial cells constitute a major player in promoting metastasis formation either by inducing the growth of tumor cells or by directing them towards dissemination in the blood or lymph. In fact, the direct and indirect interactions between tumor and endothelial cells were shown to activate several mechanisms allowing cancer cells’ invasion and extravasation. On the other side, gastrointestinal cancer development was shown to be associated with the disruption of the gut microbiome. While several proposed mechanisms have been investigated in this regard, gut and tumor-associated microbiota were shown to impact the gut endothelial barrier, increasing the dissemination of bacteria through the systemic circulation. This bacterial dislocation allows the formation of an inflammatory premetastatic niche in the distant organs promoting the metastatic cascade of primary tumors. In this review, we discuss the role of endothelial cells in the metastatic cascade of tumors. We will focus on the role of the gut vascular barrier in the regulation of metastasis. We will also discuss the interaction between this vascular barrier and the gut microbiota enhancing the process of metastasis. In addition, we will try to elucidate the different mechanisms through which this bacterial dislocation prepares the favorable metastatic niche at distant organs allowing the dissemination and successful deposition of tumor cells in the new microenvironments. Finally, and given the promising results of the studies combining immune checkpoint inhibitors with either microbiota alterations or anti-angiogenic therapy in many types of cancer, we will elaborate in this review the complex interaction between these 3 factors and their possible therapeutic combination to optimize response to treatment.